Synthesis of TEMPO radical decorated hollow porous aromatic frameworks for selective oxidation of alcohols. Issue 7 (4th January 2021) - Shen, Yan-Ming; Xue, Yun; Yan, Mi; Mao, Hui-Ling; Cheng, Hu; Chen, Zhuo; Sui, Zhi-Wei; Zhu, Shao-Bin; Yu, Xiu-Jun; Zhuang, Jin-Liang
Abstract : A bottom-up approach was developed to prepare TEMPO radical decorated hollow aromatic frameworks (HPAF-TEMPO), which enable the aerobic oxidation of a broad range of alcohols with high efficiency and excellent selectivity. Abstract : A bottom-up approach was developed to prepare TEMPO radical decorated hollow aromatic frameworks (HPAF-TEMPO) by using TEMPO radical functionalized monomers and SiO2 nanospheres as templates. The accessible inner layer, high density of TEMPO sites, and hybrid micro-/mesopores of the HPAF-TEMPO enable the aerobic oxidation of a broad range of alcohols with high efficiency and excellent selectivity.